2023
DOI: 10.3233/prm-220014
|View full text |Cite
|
Sign up to set email alerts
|

Stress among mothers of children with Autism Spectrum Disorder in comparison to children with & without special health care needs

Abstract: PURPOSE: Parenting a child with special health care needs (SHCN) is often stressful. This study aimed to measure and compare stress among mothers of children with (a) Autism Spectrum Disorder (ASD) - ASD group, (b) Developmental delay without ASD group, (c) SHCN without developmental delay group, and (d) Typically developing group. To assess factors associated with maternal stress in children with developmental disorders. METHODS: A cross-sectional analytical study was performed with children aged 2–12 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Growing evidence points to the frequent occurrence of mental disorders in close relatives of autistic patients, highlighting cross‐generational associations between parental psychiatric illness and ASD in offspring (Birmaher et al, 2010; Chien et al, 2022; Liang et al, 2021), as well as common neurodevelopmental abnormalities (e.g., cognitive, learning, coordination, social, or emotional disturbances) among the siblings of individuals with ASD (Lauritsen et al, 2005; Lin et al, 2022; Pisula & Ziegart‐Sadowska, 2015). Also, recent findings suggest worsened parental well‐being measures to be consistently associated with the severity of the autistic child's clinical picture (Lanyi et al, 2022; Lohiya et al, 2023; Valicenti‐McDermott et al, 2015). Moreover, mainly due to their socio‐communicative difficulties and atypical interests and/or behaviors, adolescents with ASD are often exposed to aggressive peer victimization and bullying (Hoover & Kaufman, 2018), which are commonly recognized as risk factors for exacerbated ASD core symptoms and comorbid psychopathologies (Cappadocia et al, 2012; Fuld, 2018; Taylor & Gotham, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence points to the frequent occurrence of mental disorders in close relatives of autistic patients, highlighting cross‐generational associations between parental psychiatric illness and ASD in offspring (Birmaher et al, 2010; Chien et al, 2022; Liang et al, 2021), as well as common neurodevelopmental abnormalities (e.g., cognitive, learning, coordination, social, or emotional disturbances) among the siblings of individuals with ASD (Lauritsen et al, 2005; Lin et al, 2022; Pisula & Ziegart‐Sadowska, 2015). Also, recent findings suggest worsened parental well‐being measures to be consistently associated with the severity of the autistic child's clinical picture (Lanyi et al, 2022; Lohiya et al, 2023; Valicenti‐McDermott et al, 2015). Moreover, mainly due to their socio‐communicative difficulties and atypical interests and/or behaviors, adolescents with ASD are often exposed to aggressive peer victimization and bullying (Hoover & Kaufman, 2018), which are commonly recognized as risk factors for exacerbated ASD core symptoms and comorbid psychopathologies (Cappadocia et al, 2012; Fuld, 2018; Taylor & Gotham, 2016).…”
Section: Discussionmentioning
confidence: 99%
“… 33 - 35 The long-term struggle of premature babies in the neonatal intensive care unit (NICU) and the persistence of chronic diseases lead to a very tiresome process for the family. In the study conducted by Lohiya et al, 36 it was reported that mothers of children with ASD had higher stress compared to mothers of children who had developmental delay without ASD, mothers of children with care needs who did not have developmental delay, and mothers of children who were typically developing. The increased needs of children with ASD and the responsibility of parents to meet these needs can complicate the life of the families.…”
Section: Discussionmentioning
confidence: 98%